The Influence of Product Innovation, Marketing Strategy, and Entrepreneurship Orientation on Sharia Hotel Marketing Performance in the Covid-19 Pandemic Period with Competitive Advantage as an Intervening Variable - Bolot Wiji Prasetiyo; Imanda Firmantyas Putri Pertiwi (Profesional Muda Cendekia Publishing, 2021)
This study aims to determine the effect of product innovation, marketing strategy, entrepreneurial orientation on the marketing performance of sharia hotels during the Covid-19 pandemic with competitive advantage as an intervening variable. This research is a type of quantitative research and the data used are primary data. The population in this study were employees of Hotel Arini Syariah Solo, Hotel Anuggrah Syariah Boyolali, and Oemah Djari Hotel Syariah Salatiga. The sample in this study amounted to 30 respondents, namely employees who work in the marketing division and employees related to Islamic hotel marketing. The analytical method used is the Path Analysis method with the help of the SPSS-21 program tool. The results of this study are product innovation, marketing strategy, entrepreneurial orientation, and competitive advantage have no effect on the marketing performance of sharia hotels during the Covid-19 pandemic. Marketing strategy has a positive and significant impact on the competitive advantage of sharia hotels. Product innovation and entrepreneurial orientation have no effect on competitive advantage. Competitive advantage cannot mediate the influence of product innovation, marketing strategy, and entrepreneurial orientation on marketing performance